Complete genome and functional insights into Microbacterium sp. strain FBCC-B4120, a novel freshwater isolate with diverse biotechnological traits - Jina Kim; Hyaekang Kim; Jaeduk Goh; Chun-Zhi Jin; Hyung-Gwan Lee; Chang Soo Lee; Sanghwa Park; Eu Jin Chung; Yejin Park; Seungmin Shin; Youngmin Han; Woori Kwak (PLoS ONE, 2026)
The genus Microbacterium encompasses a diverse group of Actinobacteria with broad ecological distribution and functional versatility. Here, we report the complete genome sequence of Microbacterium sp. FBCC-B4120, a novel strain isolated from a freshwater ecosystem in Korea. The genome was assembled into a single circular chromosome of 3.78 Mb with a G + C content of 70.5%, achieving 100% genome completeness. Phylogenomic analysis confirmed that FBCC-B4120 represents a distinct species within the genus, with M. thalassium identified as its closest relative. FBCC-B4120 demonstrated diverse physiological activities such as antimicrobial activity, siderophore production, glycosidase activity, and traits associated with anti-obesity and antiviral effects. Comparative genome analysis revealed a broad repertoire of carbohydrate-active enzymes and a distinct urea utilization cluster, suggesting expanded capacities for carbohydrate metabolism and nitrogen utilization. These findings establish FBCC-B4120 as a novel Microbacterium species with distinctive genomic features and multifunctional traits, highlighting its potential as a valuable resource for future biotechnological applications. However, the functional predictions presented here rely primarily on genomic annotation, and further biochemical validation will be required to confirm these activities.